Tracing Ruskin’s Threads: Legacies in Linen, Lace and Place - Dickinson, Rachel; Kelly, Déirdre (English Literature)
Drawing on cultural textile legacies from Venice and historic Lancashire, this paper demonstrates how Ruskin was inspired by cloth and used the language of lace to convey wider messages. Tracing threads, both of his instructions and of Venice Lace, the paper briefly considers how these resonate with the nineteenth century revival of Lakeland Linen and Lace. Co-authored by an academic and a visual artist, the paper takes a transdisciplinary approach, coupling traditional scholarship with practice research responses to Ruskin, lace and place.